Contemporary slavery: researching child domestic servitude - Derby, C. Nana (Univ. Press of America, 2009)
Introduction and need for the study -- Children's childhood, rights, and child labor exploitation -- Research methods -- Processes of recruitment and the nature of relationships between domestic servants and their employers -- Culture of Ghana and its impact on child domestics -- Child domestic servitude as a household survival strategy -- Relationship between formal education and the incidence of child domestic servitude -- Child domestic servitude : the question on contemporary slavery -- Conclusions : historical and domestic and economic explanations of contemporary child domestic servitude